1996
DOI: 10.1128/jvi.70.11.7398-7413.1996
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that the UL84 gene product of human cytomegalovirus is essential for promoting oriLyt-dependent DNA replication and formation of replication compartments in cotransfection assays

Abstract: The protein products of 11 viral genomic loci cooperate in a transient cotransfection assay to mediate lytic-phase DNA replication of oriLyt, the human cytomegalovirus (HCMV) origin of replication. Six of these genes have homology with the well-characterized herpes simplex virus replication genes and encode core replication machinery proteins that are typically essential for DNA synthesis. The remaining five HCMV gene loci, initially referred to as auxiliary components, include several known immediate-early (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
50
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(53 citation statements)
references
References 94 publications
(138 reference statements)
3
50
0
Order By: Relevance
“…Moreover, all Herpesviruses have a common replicative complex characterized by highly conserved groups of replication and recombination proteins (Rennekamp and Lieberman, 2010). In fact, many of these proteins can be interchanged between different Herpesviruses; for example, Epstein-Barr virus proteins have been shown to replicate human cytomegalovirus (Sarisky and Hayward, 1996). In DNA viruses, recombination also plays an important role in the repair of DNA damage, especially in the latency stage (Wilkinson and Weller, 2004) but, paradoxically to previous observations, the analysis of complete genomes of many Herpesviruses has shown that the repair-initiating DNA sequences differ between aand c-Herpesviruses, thus suggesting possible differences in the recombination mechanisms between these two subfamilies (Brown, 2014).…”
Section: Recombination In Dna Virusesmentioning
confidence: 99%
“…Moreover, all Herpesviruses have a common replicative complex characterized by highly conserved groups of replication and recombination proteins (Rennekamp and Lieberman, 2010). In fact, many of these proteins can be interchanged between different Herpesviruses; for example, Epstein-Barr virus proteins have been shown to replicate human cytomegalovirus (Sarisky and Hayward, 1996). In DNA viruses, recombination also plays an important role in the repair of DNA damage, especially in the latency stage (Wilkinson and Weller, 2004) but, paradoxically to previous observations, the analysis of complete genomes of many Herpesviruses has shown that the repair-initiating DNA sequences differ between aand c-Herpesviruses, thus suggesting possible differences in the recombination mechanisms between these two subfamilies (Brown, 2014).…”
Section: Recombination In Dna Virusesmentioning
confidence: 99%
“…Origin-dependent replication of HCMV in primary human cells requires the gene products of the core replication open reading frames in addition to UL36-38, UL112-113, IE1/IE2 and UL84 (22,27). In Vero cells, however, UL84 appears to be the only non-core replication protein required for oriLyt-dependent replication (27).…”
mentioning
confidence: 99%
“…Initially, UL84 was shown to be 1 of 11 loci required for oriLyt-dependent DNA replication (22). More recently, this observation was underscored by Sarisky and Hayward, who demonstrated that UL84 plays a critical role in transient replication (27). The exact function of the UL84 protein in DNA replication remains unknown.…”
mentioning
confidence: 99%
“…After PCR amplification, the DNA product was cleaved with the appropriate restriction endonucleases and subcloned into pRTS2 as follows: pRTS11, -12, -13, -14, -15, -16, -25, and -28 as XbaI-HindIII fragments and pRTS21 as a BamHI-BglII fragment. These plasmid constructions have been described previously (58), as has the origin-containing plasmid, pSL77 (19).…”
Section: Methodsmentioning
confidence: 99%